Primary renal aspergillosis in a newborn: a case report and review of the literature on children - Maquera-Afaray, Julio; Luna-Vilchez, Medalit; Portillo-Alvarez, Diana; López, José W (The Turkish Journal of Pediatrics, 2022)
Background. Primary renal aspergillosis is uncommon and mainly affects people with immune system impairment and/or genitourinary disease. Case. We report the case of a male newborn with Down syndrome and congenital heart disease, who underwent surgery for anorectal malformation and presented persistent fever and impaired kidney function secondary to kidney abscesses due to Aspergillus. The patient responded favorably to antifungal treatment and percutaneous drainage but died following heart surgery. Conclusions. To the best of our knowledge, only seven cases of renal aspergillosis have been reported in children worldwide, this being the second in a newborn. Aspergillus species must be considered among the fungal etiological agents of genitourinary tract infections in order to establish adequate antifungal treatment to achieve therapeutic success against filamentous fungi.